CHRONIC RENAL FAILURE: CLINICAL CASE ANALYSIS - Pereira Montenegro, Michellly; Scremin, Marlete; Corrêa Monteiro, Sylmara; Raissa de Souza, Kellen; Carvalho Fernandes, Valéria; Gonçalves Soares, Davidson; Almeida Cavalcanti Magalhães, Weslane; Cordeiro de Souza Ferreira, Joyce; Maciel, Reginalda; Martins Souza, Sarah; Glória dos Santos, Paulielly; Guilherme Pereira, Victor; et al. (Health and Society, 2024)
Objective: to describe the concepts and characteristics, epidemiology of chronic renal failure, causes, clinical manifestations, treatment, pathophysiology and nursing care for patients with chronic renal failure. Materials and methods: the approach of the work was done through a clinical-problem case study. Scientific articles were searched to effectively respond to the case study. Results and discussion: the documentary analysis allowed the elaboration of seven categories that deal with renal failure, which responded appropriately to the clinical case. Final Considerations: the nursing team has the duty to administer the treatment to the patient, guide the family and the same in relation to the therapy instituted, monitor the patient’s response to treatment, monitoring the vital signs and potential complications in a synergistic work with the medical team.